2008
DOI: 10.1111/j.1572-0241.2007.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

ATG16L1andIL23RAre Associated With Inflammatory Bowel Diseases but Not With Celiac Disease in The Netherlands

Abstract: We confirmed the association of IL23R and ATG16L1 with CD susceptibility and also the association of IL23R with UC. We found IL23R and ATG16L1 were not associated with celiac disease susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 36 publications
2
57
1
Order By: Relevance
“…Interestingly, in a very recent study McCarroll et al 56 have shown that the causal variant responsible for IRGM Figure 1 Pooled data for the ATG16L1 rs2241880 susceptibility allele frequency (SAF). (a) Pooled data of Australian, 39 Belgian, 16 British, 14,21,23,25 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 27,33 Hungarian, 34 Japanese, 22 New Zealander, 26 North American 15,24 and Spanish cohorts for Crohn's disease (CD). (b) Pooled data of Australian, 39 British, 21,23,37 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 33 Hungarian, 34 New Zealander, 26,39 North American 15 and Spanish cohorts for ulcerative colitis (UC).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in a very recent study McCarroll et al 56 have shown that the causal variant responsible for IRGM Figure 1 Pooled data for the ATG16L1 rs2241880 susceptibility allele frequency (SAF). (a) Pooled data of Australian, 39 Belgian, 16 British, 14,21,23,25 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 27,33 Hungarian, 34 Japanese, 22 New Zealander, 26 North American 15,24 and Spanish cohorts for Crohn's disease (CD). (b) Pooled data of Australian, 39 British, 21,23,37 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 33 Hungarian, 34 New Zealander, 26,39 North American 15 and Spanish cohorts for ulcerative colitis (UC).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][21][22][23][24][25][26][27][28][29][30][31][32][33][34]38,39 Funnel plots and Egger tests were performed to analyse the publication bias of the meta-analysis. No statistically significant values were observed in CD studies (P ¼ 0.6) or UC studies (P ¼ 0.4), with symmetric funnel plots for both studies (Supplementary Figure 1).…”
Section: Association Of Atg16l1 and Irgm With Ibd Rj Palomino-moralesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous GWAS reports have identified several SNPs that regulate or communicate with the autophagic pathways and represent risk factors for Crohn disease. 7,[52][53][54][55][56][57][58] For instance, the SNPs in NOD2 are the most prominent risk-associated SNPs and can lead to early disease onset and a more complicated clinical course of Crohn disease, including fibrostenosis and fistulization. 11 These genetic variations also exhibit a marked reduction in bacterial autophagy due to the fact that NOD2 recruits ATG16L1 to the site of bacterial entry, 10 as described in more detail below.…”
Section: Atg16l1 and Susceptibility To Crohn Diseasementioning
confidence: 99%
“…Both CD and UC were associated with IL23R in a study conducted in over 500 Dutch patients with IBD [38]. In another study involving Korean patients with CD, two other polymorphisms (rs1004819 and rs1495465) were significantly associated with CD, and when the genotype was correlated to the disease phenotype, it was found that it was associated with both stricturing and penetrating disease [39].…”
Section: Th-17/il-23 Cytokine Responsesmentioning
confidence: 96%